ROBUST DESIGN OF CRASH CUSHION ENERGY-ABSORBING BOX BASED ON THE CRASHWORTHINESS TOPOLOGY OPTIMIZATION - HUANG YuPeng; SONG Jie; LEI ZhengBao (Jixie qiangdu, 2020)
In order to improve the crashworthiness of the crash cushion energy-absorbing box,firstly,this paper established the"vehicle-crash cushion"FE models of frontal impact,offset impact,oblique impact and frontal side impact in accordance with the regulations,and then a crashworthiness topology optimization method of cellular automata was used for the energyabsorbing box topology optimization in the transverse and longitudinal extrusion constraint respectively,the optimized results show that the obtained beam configuration in the longitudinal extrusion constraint is different from the barrel configuration in the transverse extrusion constraint and it performs better in the crashworthiness. Secondly,taking into account the effects of the design variable uncertainties on the crashworthiness target responses,a multiobjective robust optimization combined with Taguchi method and satisfaction function was carried out for the optimization design of the new beam energy-absorbing box. The results show that the acceleration of the optimized energy-absorbing box is 106. 6 m/s~2,less than 200 m/s~2,it is in good safety performance; SEA is 2. 54 kJ/kg,it improves 32. 8% than before optimization; the total satisfaction increases 30. 4%,it greatly enhances the robustness of the energy-absorbing box.